Special Edition to Commemorate The Conferment Of Honorary Doctor of Science to Prof Atta Ur-Rahman, FRS in conjunction with UiTM's 75th Convocation : Dewan Agong Tuanku Canselor : 20 October 2011 / Jabatan Komunikasi Korporat, UiTM - Jabatan Komunikasi Korporat, UiTM (Jabatan Komunikasi Korporat, UiTM, 2011)
It is with great pleasure that I welcome our guests, parents and relatives of graduands, to this momentous occasion of UiTM's 75th Convocation Ceremony. I am sure that such a pleasure is shared by all of our 189,000 students and our 17,000-strong working fraternity. Congratulations are also in order to all graduating students, in Shah Alam and four state campuses. It is my wish that this convocation will strengthen our will to sustain a life of peace and harmony in our beloved Malaysia. To all graduating students: You have all done us proud for having successfully overcome every trial and tribulation throughout this journey, in your quest for knowledge in UiTM.For so long, Dewan Sri Budiman had been witness to hundreds of convocation ceremonies which saw thousands of students walking up the aisle to the stage to receive their scroll. Last year, for the first time, this historical event was repeated in the four state campuses of UiTM Perlis, Perak, Terengganu and Sarawak, along with the main ceremony taking place in Shah Alam. This year, the convocation in Shah Alam is held in our new Dewan Agong Tuanku Canselor (DATC), named in honour of our Royal Chancellor, the Yang di-Pertuan Agong.